2008
DOI: 10.1007/s10535-008-0138-9
|View full text |Cite
|
Sign up to set email alerts
|

Specific activation of PR-10 pathogenesis-related genes in apple by an incompatible race of Venturia inaequalis

Abstract: Apple (Malus × domestica Borkh. cv. Golden Delicious) trees were inoculated with fungal pathogens, corresponding either to an incompatible strain of Venturia inaequalis or to non-host pathogens (Venturia pyrina, Alternaria brassicicola) in order to characterize the regulation of PR-10 genes in these different situations in relationship to symptom development. Macro-and microscopic observations of the plant-fungus interactions revealed typical symptoms of resistance with V. inaequalis and symptoms of hypersensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These proteins are activated in response to many different abiotic and biotic stresses [38,39] and play a putative role in plant defence responses to pathogens [17,40,41]. Indeed, Mal d 1 proteins are also known as pathogenesis-related proteins of class 10 (PR-10s) [41].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are activated in response to many different abiotic and biotic stresses [38,39] and play a putative role in plant defence responses to pathogens [17,40,41]. Indeed, Mal d 1 proteins are also known as pathogenesis-related proteins of class 10 (PR-10s) [41].…”
Section: Discussionmentioning
confidence: 99%
“…The PR10 genes can be activated by the biotic stresses, such as microbial attacks, fungal elicitors, or wounding stresses, as well as abiotic stresses, such as salt and drought (Choi et al, 2012). In particularly, it has been shown that PR10 from apple (Malus domestica) was activated when exposed to the pathogens, such as viruses and fungi (Pühringer et al, 2000;Poupard et al, 2003;Chevalier et al, 2008;Liu et al, 2021), acibenzolar-S-methyl (ASM) (Ziadil et al, 2001), ethephon, and wounding (Poupard et al, 2003), indicating that in apple, PR10 plays an important role in response to the biotic and abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that NtWRKY4 is involved in tobacco TMV-disease resistance. These results led us to examine the expression levels of pathogen-related genes PR1 and PR2, which are reliable molecular markers of systemic acquired resistance (SAR) (Benedetti et al 1998, Chevalier et al 2008, Jaakola et al 2008. Initial examination of the expression of PR genes revealed that RNAi transgenic line 3 and line 12 and vector control produced no detectable mRNA for PR1 and PR2 under normal growth conditions (data not shown).…”
Section: Resultsmentioning
confidence: 99%